Tarjuma-yi Kitāb al-Nijāra : Dar handasa-yi ʿamalī - Būzjānī, Abu ʼl-Wafāʾ, (Miras Maktoob, ISBN: 9789004365452., 2019)
Abu ʼl-Wafāʾ Būzjānī (d. 388/998) was a mathematician and astronomer and a native of Būzjān near Nishapur. He studied arithmetic with two of his uncles, probably in Būzjān. When he was nineteen years old he went to Baghdad. There he further developed himself to become one of the leading scientists of his age, working at the Buyid court. He was a contemporary and protector of the chronicler of intellectual and artistic life in Baghdad at the time, Abū Ḥayyān al-Tawḥīdī (d. ca. 414/1023). In the bibliographical literature more than twenty works are ascribed to him, many of which were lost. The present work was originally written in Arabic under the title Kitāb fī mā yaḥtāj ilayhi ʼl-ṣāniʿ fī aʿmāl al-handasa . It is a groundbreaking work in that Būzjānī was the first to write a monograph on practical geometry as justified by the rules of theoretical geometry. Medieval Persian and French translation, with introductions and notes.